THE EFFECTS OF MAGNETISM ON LIVING ORGANISMS (Modern education and development, 2025)
Magnetic fields (MFs) have been shown to influence various biological systems, from microorganisms to humans. This article reviews the current understanding of how static and dynamic magnetic fields affect cellular processes, growth, and behavior in living organisms. Studies suggest that magnetism can alter enzyme activity, gene expression, and neural functions, though the mechanisms remain under investigation. Further research is needed to fully understand the biological implications of magnetic exposure fully.